2016
DOI: 10.1021/acschemneuro.6b00029
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Multiparameter Optimization Desirability: Application in Drug Discovery

Abstract: Significant progress has been made in prospectively designing molecules using the central nervous system multiparameter optimization (CNS MPO) desirability tool, as evidenced by the analysis reported herein of a second wave of drug candidates that originated after the development and implementation of this tool. This simple-to-use design algorithm has expanded design space for CNS candidates and has further demonstrated the advantages of utilizing a flexible, multiparameter approach in drug discovery rather th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
406
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 405 publications
(434 citation statements)
references
References 13 publications
(35 reference statements)
4
406
0
1
Order By: Relevance
“…After the discovery by Weggen et al [31] that a subset of NSAIDs could selectively lower Aβ 42 without affecting the initial cleavage step by GS (ε cleavage), a lot of research was dedicated to finding new generations of compounds that could mediate similar effects [20, 32]. In our quest to discover GSMs that satisfy all known empirical rules of good central nervous system (CNS) drug-like properties [4143], we synthesized FRM-36143 (Bursavich MG, Harrison BA, Costa DE, Hodgdon HE, Freeman EA, Hrdlicka LA, Kapadnis S, Moffit J, Murphy DA, Patzke H, Tang C, Wen M, Burnett DA, Koenig G, Blain JF. Design, synthesis and evaluation of a novel series of oxadiazine Gamma Secretase Modulators for familial Alzheimer’s disease, Submitted).…”
Section: Discussionmentioning
confidence: 99%
“…After the discovery by Weggen et al [31] that a subset of NSAIDs could selectively lower Aβ 42 without affecting the initial cleavage step by GS (ε cleavage), a lot of research was dedicated to finding new generations of compounds that could mediate similar effects [20, 32]. In our quest to discover GSMs that satisfy all known empirical rules of good central nervous system (CNS) drug-like properties [4143], we synthesized FRM-36143 (Bursavich MG, Harrison BA, Costa DE, Hodgdon HE, Freeman EA, Hrdlicka LA, Kapadnis S, Moffit J, Murphy DA, Patzke H, Tang C, Wen M, Burnett DA, Koenig G, Blain JF. Design, synthesis and evaluation of a novel series of oxadiazine Gamma Secretase Modulators for familial Alzheimer’s disease, Submitted).…”
Section: Discussionmentioning
confidence: 99%
“…The CNS MPO desirability method is quite simple, with parameters derived from medicinal chemistry best practices, and it is able to balance multiple variables while avoiding hard cut-offs. It demonstrated a good correlation between a high score (> 4 out of a possible max of 6) and good in vitro ADME properties [12,78]. …”
Section: Tpsa In Mpomentioning
confidence: 90%
“…Scientists at Pfizer have recently shown that use of their CNS Multi-Parameter Optimisation (MPO) scoring tool has increased the percentage of clinical candidates discovered that possess desirable ADMET properties and cross the BBB [15]. This tool assigns a desirability score (0.05-1) for six physicochemical properties: MW; lipophilicity, calculated partition coefficient (cLogP); distribution coefficient at pH = 7.4 (cLogD); most basic centre (pKa); number of hydrogen bond donors (HBD) and topological polar surface area (TPSA) [16].…”
Section: Scoring Metrics For Cns Drugsmentioning
confidence: 99%
“…In their original study, the authors showed that a set of 119 marketed CNS drugs had generally higher CNS MPO scores than a set of 108 Pfizer CNS candidates [16]. Moreover, after routine application of the tool, nominated CNS candidates had been shifted towards more polar and less lipophilic property space [15]. Simplicity of application and a clear mechanistic link allow chemists to understand how modification of molecular structure changes the CNS MPO score.…”
Section: Scoring Metrics For Cns Drugsmentioning
confidence: 99%